BERINGIAN CLIMATE DURING THE LATE PLEISTOCENE AND HOLOCENE - Alfimov A.V; Berman D.I (My University, 2001)
The difference between the climates of the Bering Land Bridge and Asiatic (western) Beringia 18–20 ka ago is discussed. The climatic reconstructions of the Bering Land Bridge and western Beringia are based upon two methods. First, we discuss the ecological and thermal requirements of the thermophilic weevils (Coleoptera: Curculionidae) in the genus Stephanocleonus. Second, we discuss the effect of climatic continentality on soil temperatures. We suggest that for western Beringia, the climate was suitable for the warm steppe environment – mean July air temperatures were at least 10–11°C, and an annual sum of daily temperatures above 0°C (SDD) at the soil surface was up to 2500°C. In contrast to these conditions, the climate of the Bering Land Bridge was very similar to that found in the modern Arctic tundra zone.
Keywords: Holocene; Pleistocene; climates; Bering Land Bridge; Asiatic Beringia; Cenozoic::Quaternary::Holocene; Cenozoic::Quaternary::Pleistocene; Кайнозой::Четвертичная::Голоцен; Кайнозой::Четвертичная::Плейстоцен